Peran Perempuan Dalam Mensejahterakan Ekonomi Keluarga Perspektif Hukum Ekonomi Syariah - Muhamad Ali Tamrin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Individually working is obligatory to meet the needs of oneself and the person he is responsible for, in the family who is obliged to be the backbone is a husband specifically in fulfilling household needs, a case where many traders who are dominated by mothers do not necessarily become slavery in the household to be responsible for meeting household needs, in the Canggu Badas Village Manufacturing Market, Kediri Regency, it has been found that the motivation to trade includes; because of the hobby factor, the desire factor to participate in helping the husband and become an independent or self-earning woman. In addition, the factor of religious understanding because work is a field of worship. However, even so, Islam provides restrictions on the existence of permission and blessings from the husband because the essence of a woman in the household is as the mother of her children. And it should not be negligent as a result of the mother's work.